THE ISSUES AND CHALLENGES OF SUSTAINABLE AGRICULTURE DEVELOPMENT IN INDIA (International Journal of Food and Nutritional Sciences, 2022)
The objectives of the study are to find the trends and issues and challenges with status of the agricultural sector, to identify areas of intervention that could achieve sustainable agricultural growth, and to find the future prospects and solution for India. The study is collected all the secondary data which includes books journals, newspaper and Web Pages. The study concluded that Indian agriculture is the largest private sector. Agriculture dominates India because it is linked to production, processing, and marketing. Using secondary data, the report examines agriculture's sustainable development. India's rural population relies on agriculture. Sustainable agriculture development increases productivity, efficiency, and employment while preserving natural resources. Multiple agricultural systems, deforestation, and other factors prevent soil degradation.